PENGARUH TIPE KEPRIBADIAN TERHADAP INTENSI MEMBELI DENGAN PENYAJIAN MODEL PERSUASI HEURISTIK-SISTEMATIK - Ika Rahma Susilawati; Ika Adita Silviandari (MANASA, 2012)
This experimental research was conducted to determine the influence of DISC personality types and types of advertising presentation (heuristic and sysematic) to consumers buying intention of “M.G Product this study aimed to determine how the effect of the DISC personality types associated with the formation of consumer behavior (consumer response to a new product). Subjects were 70 students of psychology, faculty of political and social science Universitas Brawijaya Malang. The experimental design used was mathcing group design. Treatments conducted in the form of “Mr. G” advertising presentation exposure designed in two modes of persuasion, i.e the heuristic advertising mode (experimental  group 1) and systematic advertising mode (experimental group 2). The result of statistical analysis using factorial anova shown there is no significant differences between each of D,I,S,C personality types with – heurisitic and systematic- type of advertising presentation in the buying intention of new products “Mr.G”